MODIFIKASI TEPUNG PISANG â€œMULU BEBEâ€ (Musa acuminata) INDIGENOUS HALMAHERA UTARA SEBAGAI SUMBER PANGAN PREBIOTIK - Lumba, Ronal; Djarkasi, Gregoria; Molenaar, Robert (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2017)
"Mulu bebe" plantain (Musa acuminata) is a potential tropical fruit commodity in Indonesia, especially in the North Halmahera area where it can be used as part of food diversification. It is orange in color and no study has been done so far regarding physicochemical properties of starch and its resistant starch. This research was aimed to study the physical properties of â€œMulu bebeâ€ plantain flour modified through a spontaneous fermentation process combined with heating and cooling to increase the resistant starch content for use as a prebiotic food source. This study was designed as a completely randomized experiment (CRD) having 2 factors and three replications. The first factor is the spontaneous fermentation time consist of 0, 12, 24 and 36 hours and the second factor is without (0 minutes) and with 45 minutes heating. The result of length of fermentation time showed the lactic acid bacteria grow well during 36 hours fermentation, reaching 8,6 log cfu/ ml. Spontaneous fermentation process alone aid no effect on the physicochemical properties of flour produced, but the presence of heating and cooling process was significantly modified the physicochemical properties. Through the process of 36 hours fermentation, followed by heating at a temperature of 121oC for 45 minutes and cooling at 4 Â°C for 24 hours produced resistant starch content of 48.53% and in vitro starch digestibility 21,94%.